E-Learning and Motivation: A Case Study on Students and Instructors at Duhok University - Suzan Sherzad Mohammed-Salih Alsoufi (Zanco Journal of Humanity Sciences)
This research investigates the efficacy of E-learning as an instructional tool in higher education, emphasizing the adoption of contemporary Information and Communication Technologies (ICTs) in the EFL classrooms. It provides a comprehensive scholarly foundation by reviewing relevant literature and evaluating specific contributions from academics regarding E-learning, particularly its application in the teaching and learning process within the higher education context. Recognizing motivation as a crucial determinant of successful learning, the study identifies key motivating factors and explores ways for their integration to amplify student performance. The study is conducted by relying on data collection, involving an open-ended questionnaire administered to sixty participants across diverse departments at Duhok University. The findings demonstrate that there is a strong endorsement for integrating ICTs into conventional classrooms, highlighting their contribution to developing digital skills and establishing interactive, personalized, and globally interconnected learning environments. Participants recognize E-learning’s benefits, including adaptability and accessibility, but they also express concerns about potential limitations on personal development, social relationships, digital literacy challenges, and specific infrastructural constraints in Kurdistan. The data also underscores motivation’s pivotal role in online learning success, proposing approaches like interactive resources, cooperation fostering, technical assistance provision, and measures to enhance intrinsic motivation. The recommendations seek to improve the general quality of online learning in educational institutions, specifically in the context of the Kurdistan Region of Iraq.